METODE SYSTEMATIC LITERATURE REVIEW UNTUK PENTINGNYA KARYA ILMIAH DALAM PENDIDIKAN TINGGI - Nurhidayah Nurhidayah; Usiono Usiono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Scientific work is defined as the results of published research that contribute to the development of science. This study aims to explore the importance of scientific work in the context of higher education through a systematic literature review method. The method used in this study involves the collection, evaluation, and analysis of relevant articles from various academic databases. The findings indicate that scientific work plays a crucial role in improving the quality of education, facilitating further research, and strengthening collaboration between institutions. The discussion highlights the challenges faced in the publication and accessibility of scientific work, as well as the implications for the development of higher education curricula. This study emphasizes the importance of integrating scientific work into the teaching and learning process to produce competitive and innovative graduates. The results show that integrating scientific work into the higher education curriculum can increase the relevance of education to the needs of industry and society. The conclusions of this study emphasize the need for better strategies in supporting the publication of scientific work, as well as the importance of strengthening collaboration between educational institutions and the industrial sector to maximize the impact of scientific work in education.